Acute care rehabilitation utilization, access, and outcomes among hospitalized adults with traumatic brain injury - Bukhari, Rayyan A., author; Graham, James, advisor; Weaver, Jen, committee member; Davalos, Deana, committee member; Sharp, Julia, committee member (Colorado State University. Libraries, 2024)
Objective: The purpose of this dissertation was to conduct three research studies aimed at gaining a comprehensive understanding of the barriers and facilitators to equitable access to and timing of rehabilitation services, community discharge, and unplanned 90-day post-discharge hospital readmission among individuals hospitalized with Traumatic brain injury (TBI). Introduction: There are approximately 2.5 million TBI-related emergency department visits, 288,000 TBI-related hospitalizations, and 61,000 TBI-related deaths reported each year (Centers for Disease Control and Prevention, 2019). TBI is associated with high rates of disability, including limitations in performing basic activities of daily living (ADLs), such as self-care, and/or in performing physical tasks, such as mobility (Klima et al., 2019; Jessica Lo et al., 2021; Whiteneck et al., 2016). Individuals who are hospitalized with TBI should receive equitable access to multidisciplinary care, including rehabilitation services (occupational therapy [OT], and physical therapy [PT]) to address potential self-care issues, physical limitations, and cognitive deficits (National Academies of Sciences & Medicine, 2022). Early onset of acute care rehabilitation services can have positive long-term benefits for patients, including improved function, increased mobility, and enhanced quality of life (Andelic et al., 2012; Bernhardt et al., 2017; C. Y. Wang et al., 2021). A primary focus of acute care rehabilitation services is to improve patients' functional performance (Ejlersen Wæhrens & Fisher, 2007). Following acute care stays, community discharge is generally viewed as quality care indicator in acute care settings (Department of Health and Human Services [HHS], 2019). Readmission is a common concern for those who have chronic illnesses or injuries, and it is associated with higher healthcare expenses and lower quality of care (Jencks et al., 2009). Readmission rates after TBI contribute considerably to these costs, making lowering readmission rates a universal goal (Canner et al., 2016). Despite research advances and policy changes, barriers and challenges remain facing individuals with TBI (National Academies of Sciences & Medicine, 2022). Not all individuals with TBI have early access to rehabilitation services, are discharged to the community, or can avoid hospital readmission. Although several studies have addressed these issues in general population, variability in community and personal level factors among individuals with TBI need to be addressed (Office of Disease Prevention and Health Promotion & Services., 2020). Therefore, these dissertation studies are aimed at providing empirical support, further understanding, and increasing our knowledge around factors that influence individuals with TBI acute care rehabilitation services utilization and outcomes. Method: This dissertation is comprised of three studies. In Study One, we investigated how Social Determinants of Health (SDoH) impact access to and timing of rehabilitation services. Multivariable logistic and Cox regression analyses (i.e., time-to-event analyses) were used to calculate odds ratios for the likelihood of receiving OT and PT services, and hazard ratios for the duration to initiation of services among those who received these services. In Study Two, we explored whether the relationship between acute care OT/PT utilization and community discharge is moderated by functional or physical performance at discharge. Multivariable moderation logistic regression models were used to calculate odds ratios for the likelihood of community discharge among those who utilized OT/PT services. In both OT and PT models, we computed the main effect of OT/PT utilization on community discharge, the main effect of functional/physical (ADL/Mobility) performance scores at discharge on community discharge, and the moderating effect of ADL/mobility scores on the relationship between OT/PT utilization and community discharge. In Study Three, we examined the association between discharge functional status and unplanned hospital readmission. Logistic regression was performed to calculate odds ratios for the likelihood of unplanned 90-day hospital readmission among those who received rehabilitation services during their acute care stay. Results: In Study One, all community-level SDoH such as education attainment, income, and rurality did not show significant associations with access to or timing of acute rehabilitation services (p-values= 0.09 – 0.95). In Study Two, both ADL/mobility performance scores at discharge significantly moderated the relationship between OT/PT utilization and community discharge (ORs= 0.99, 95% CIs [0.98, 1.00]). In Study Three, neither discharge functional nor mobility scores were associated with readmission (p-values= 0.14 – 0.17). Among the three dissertation studies, several covariates such as age, presence of a significant other, race/ethnicity, health insurance type, TBI severity, length of stay, and comorbidity burden showed significant associations with access to or timing of acute rehabilitation services, community discharge, and readmission status (p-values= 0.04 – <0.001). Conclusion: Further investigations are needed to 1) ascertain whether our community-level SDoH variables, based on the first three digits of zip codes, adequately capture individual experiences and their impact on healthcare, or if community-level education, income, and rurality genuinely do not affect access to and timing of therapy services for hospitalized patients with TBI; 2) determine whether the consideration of ADL/mobility scores at discharge alone limits our understanding of the relationship, failing to encompass other patient-level factors that could either facilitate or impede a safe community discharge; and 3) determine whether discharge functional and mobility scores were too restrictive in capturing the full benefits of acute care rehabilitation services in reducing the risk of unplanned 90-day readmission risk in hospitalized patients with TBI.
Keywords: community discharge; equitable access; unplanned readmission; duration to rehabilitation services; acute care rehabilitation services; traumatic brain injury